The cumulative effect of unmet social needs on noncancerous genitourinary conditions and severity of lower urinary tract symptoms. Issue 8 (6th September 2022) - Anne Zwaschka, T.; Sebesta, Elisabeth M.; Gleicher, Stephanie; Kaufman, Melissa R.; Dmochowski, Roger R.; Reynolds, William Stuart
Abstract: Purpose: There is growing awareness on how social determinants of health may significantly influence health outcomes. The purpose of this study was to investigate the relationship between unmet social needs and the incidence and severity of multiple noncancerous genitourinary conditions. Materials and Methods: A community‐based sample of United States adults was recruited electronically to complete questionnaires on clinical and demographic information, urinary symptoms, and social needs. Logistic regression was used to assess the effect between the number of unmet social needs and various noncancerous genitourinary conditions and severity of lower urinary tract symptoms. Model was adjusted for age, gender, race, insurance, and type of living community. Results: A total of 4, 224 participants were included for final analysis. The incidence of all genitourinary conditions assessed was associated with an increasing number of unmet social needs. Additionally, having three or more unmet social needs, as compared to no needs, was associated with an increased risk of all conditions and worse symptoms—including a 23.7% increased risk of interstitial cystitis (95% confidence interval [CI] 18.8%–28.7%, p < 0.001), 21.9% risk of urge urinary incontinence (95% CI 16.8%–27.0%, p < 0.001), and 20.6% risk of overactive bladder (95% CI 15.6–25.7, p < 0.001). Conclusions: Unmet social needs are associated with an increased incidence of noncancerous genitourinary conditions as well as worse symptom severity, with multiple unmet social needs displaying a cumulative effect. These findings suggest that there is utility in screening patients for unmet social needs, and that the healthcare system should develop a more integrated approach to manage patients with urinary conditions.